AD, Volume 2, n° 2, 1977 - Full Issue - System, Abdalla S. (Africa Development, 1977)
Contents GUEST EDITORS NOTES Norman Girvart Technology : A new white Magic for Africa ? 5 La Technologie, nouvelle Magie Blanche pour l'Afrique ? ............... 8 Cadman Atta Mills Transnational Corporations, Transfer of Technology and Prospects for a « fair-deal » for Third World ................. 11 Les Sociétés Transnationales, Transfer de Technologie et Perspectives « d'arrangement équitable » pour le Tiers Monde ........... 18 ARTICLES UNCTAD Secretariat Technological Dependence : Its Nature, Consequences and Policy Implications ...................... 27 Résumé ...................... 44 P. Masette KUUYA Transfer of Technology : An Overview of the Tanzania Case ..................... 47 Résumé ........................ 70 Ilunga Ikunkamba Convention de Gestion et de Transfert de Technologie au Zaire: Le cas du cuivre ....................... 73 Summary ....................... 92 Steven Langdon Technology Transfer by Multinational Corporation in Africa: Effects on the Economy ...................... 95 Résumé ..................... 112 Shérif Mahmoud El-Hakim The Role of the Family, Kinship and Rural/Urban Migration in the Processing of Solid Waste in Cairo ................... 115 Résumé ....................... 123 DOCUMENT The Kuwait Declaration on Technical Cooperation amongst Developing Countries ........................ 125 Déclaration de Koweit sur la coopération technique parmi les nations en Développement ................... 129 BOOK REVIEWS Mark Delancey Aid and Self-Help : A General Guide to Overseas Help by Elizabeth O'Kelly ...................... 135 Michel Damaud Islam, Sociétés Africaines et Culture Industrielle, par Mamadou Dia ....................... 139 FOCUS ON RESEARCH AND TRAINING INSTITUTES African Training and Research Centre of Administration for Development, Tanger, Morocco ...................... 147 Centre for Social, Cultural and Enviroronmental Studies, University of Benin, Nigeria ....................... 151